Respiratory disability in ex-flax workers. Issue 5 (May 1986) - Elwood, J H; Elwood, P C; Campbell, M J; Stanford, C F; Chivers, A; Hey, I; Brewster, L; Sweetnam, P M
Abstract : Acute respiratory effects occur in a high proportion of subjects exposed to textile dusts. The extent to which these lead to permanent respiratory symptoms and loss of lung function is unknown. A survey of random population samples was therefore conducted in ten towns in Northern Ireland in which flax processing had been a major source of employment. The MRC questionnaire on respiratory symptoms was administered and Vitalograph tracings recorded on subjects aged 40 to 74 inclusive. An occupational history was taken at the end of each interview. Lung function in ex-flax workers was slightly lower than in control subjects never exposed to flax dust, but the presence of a positive interaction with age meant that differences were apparent only in the younger subjects. Over about the age of 65 the lung function in the ex-flax workers was comparable with that of the controls and overall the loss was at most about half that due to light smoking (1-14 cigarettes a day). The association between a "dust exposure score" and lung function was inconsistent in the two sexes. In men there was a small decrement with increasing dust exposure. In women there was also a small decrement, but a positive interaction with age meant that the women with the highest dust exposure scores had a lower loss with increasing age than the women with the least dust exposure. There was an excess in symptoms in the ex-flax workers but the size of the excess was greater than would be expected from the lung function results. It is possible that, although the survey was conducted without explicit reference to the flax industry, knowledge throughout Northern Ireland that many flax workers have been awarded compensation on the grounds of respiratory disablement may have led to an increased reporting of symptoms in the ex-flax workers.